Correlation between dietary factors and Parkinson’s disease revealed by the analysis of Mendelian randomization - Zeng, Shan; Yusufujiang, Aishanjiang; Zhang, Chunli; Yang, Chen; Li, Hongyan (Frontiers in Nutrition, 2024)
The intricate interplay between dietary habits and the development of PD has long been a subject of scientific inquiry. Mendelian Randomization (MR) emerges as a potent tool, harnessing genetic variants to infer causality in observational data. While evidence links diet to Parkinson's Disease (PD) etiology, a thorough MR exploration of dietary impacts on PD, particularly involving gut microbiota.Method:This research leverages the IEU Open GWAS project's vast GWAS database to address the knowledge gap in understanding diet's influence on PD, employing a diverse range of dietary variables. Our holistic dataset includes various foods like processed fava beans, bap, red wine, to cheese, reflecting a commitment to untangling dietary complexities in PD etiology.Advancing from initial dietary-PD associations, we innovatively explore the gut microbiota, focusing on Parabacteroides goldsteinii, in relation to bap intake and PD, employing MR. Utilizing weighted median, MR-Egger, and inverse variance weighting methods, we ensure rigorous causality assessments, meticulously mitigating pleiotropy and heterogeneity biases to uphold finding validity.Our findings indicate red wine (OR 1.031; 95% CI 1.001-1.062; p=0.044) and dried fruit consumption (OR 2.019; 95% CI 1.052-3.875; p=0.035) correlate with increased PD risk, whereas broad beans (OR 0.967; 95% CI 0.939-0.996; p=0.024) and Bap intake (OR 0.922; 95% CI 0.860-0.989; p=0.023) show protective effects against PD. Employing MR, specifically the IVW method, revealed a significant inverse association between bap intake and gut microbiota, marked by an 8.010-fold decrease in Parabacteroides goldsteinii per standard deviation increase in bap intake (95% CI 1.005 -63.818; p = 0.049). Furthermore, a connection between PD and Parabacteroides goldsteinii was observed (OR 0.810; 95% CI 0.768-0.999; p = 0.049), suggesting a potential microbiota-mediated pathway in PD etiology.Our study links dietary habits to PD risk, showing higher PD risk with red wine and dried fruit consumption, and a protective effect from broad beans and Bap. Using MR , we found bap intake inversely correlates with Parabacteroides goldsteinii in the gut, suggesting bap influences microbiota. Further, higher Parabacteroides goldsteinii levels correlate with lower PD risk, highlighting a complex interplay of diet, gut microbiome, and neurological health. These insights shed light on potential dietary interventions for PD.